Structural and Functional Characterization of a Unique AP Endonuclease From Deinococcus radiodurans - He, Yuan; Wang, Yiyi; Qin, Chen; Xu, Ying; Cheng, Kaiying; Xu, Hong; Tian, Bing; Zhao, Ye; Wang, Liangyan; Hua, Yuejin (Frontiers in Microbiology, 2020)
Various endogenous and exogenous agents cause DNA damage, including apurinic/apyrimidinic (AP) sites. Due to their cytotoxic effects, AP sites are usually cleaved by AP endonuclease through the base excision repair (BER) pathway. Deinococcus radiodurans, an extraordinary radiation-resistant bacterium, is known as an ideal model organism for elucidating DNA repair processes. Here we have investigated a unique AP endonuclease (DrXth) from D. radiodurans, and found that it possesses AP endonuclease, 3'-phosphodiesterase, 3'-phosphatase and 3'-5' exonuclease but have no nucleotide incision repair (NIR) activity. We also found that Mg2+ and Mn2+ were the preferred divalent metals for endonuclease and exonuclease activities, respectively. In addition, DrXth were crystallized and the crystals diffracted to 1.5 Å. Structural and biochemical analyses demonstrated that residue Gly198 is the key residue involved in the substrate DNA binding and cleavage. Deletion of the drxth gene in D. radiodurans caused elevated sensitivity to DNA damage agents and increased spontaneous mutation frequency. Overall, our results indicate that DrXth is an important AP endonuclease involved in BER pathway and functions in conjunction with other DNA repair enzymes to maintain the genome stability.